Development of second generation peptides modulating cellular adiponectin receptor responses - Otvos, Laszlo; Knappe, Daniel; Hoffmann, Ralf; Kovalszky, Ilona; Olah, Julia; Hewitson, Tim D.; Stawikowska, Roma; Stawikowski, Maciej; Cudic, Predrag; Lin, Feng; Wade, John D.; Surmacz, Eva; et al. (Frontiers in Chemistry, 2014)
The adipose tissue participates in the regulation of energy homeostasis as an important endocrine organ that secretes a number of biologically active adipokines, including adiponectin. Recently we developed and characterized a first-in-class peptide-based adiponectin receptor agonist by using in vitro and in vivo models of glioblastoma and breast cancer (BC). In the current study, we further explored the effects of peptide ADP355 in additional cellular models and found that ADP355 inhibited chronic myeloid leukemia (CML) cell proliferation and renal myofibroblast differentiation with mid-nanomolar IC50 values. According to molecular modeling calculations, ADP355 was remarkably flexible in the global minimum with a turn present in the middle of the peptide. Considering these structural features of ADP355 and the fact that adiponectin normally circulates as multimeric complexes, we developed and tested the activity of a linear branched dimer (ADP399). The dimer exhibited approximately 20-fold improved cellular activity inhibiting K562 CML and MCF-7 cell growth with high pM - low nM relative IC50 values. Biodistribution studies suggested superior tissue dissemination of both peptides after subcutaneous administration relative to intraperitoneal inoculation. After screening of a 397-member adiponectin active site library, a novel octapeptide (ADP400) was designed that counteracted 10-1000 nM ADP355- and ADP399-mediated effects on CML and BC cell growth at nanomolar concentrations. ADP400 induced mitogenic effects in MCF-7 BC cells perhaps due to antagonizing endogenous adiponectin actions or acting as an inverse agonist. While the linear dimer agonist ADP399 meets pharmacological criteria of a contemporary peptide drug lead, the peptide showing antagonist activity (ADP400) at similar concentrations will be an important target validation tool to study adiponectin functions.